Determinants of Physical Activity Engagement in Riau Province, Indonesia: A Cross-Sectional Study Based on the Andersen Behavioral Model - ., Mishbahuddin; Rungsihirunrat, Kanchana (Journal of Posthumanism, 2025)
Increasing physical activity is one of the health behaviors that are the emphasis of Indonesia’s national policy on non-communicable diseases (NCDs). But putting this policy into practice will be difficult, especially when it comes to encouraging physical activity as part of the NCD plan. This study examines factors influencing physical activity engagement in Riau Province, Indonesia, using the Andersen Behavioural Model. A cross-sectional study was conducted in Riau Province from February to September 2024, using a questionnaire distributed to communities across twelve districts. Participants aged 15-59, recruited through cluster random sampling. Data were collected on demographic, health system support, and individual/family factors related to physical activity. To find important factors, logistic regression and descriptive statistics were employed. The dependent variable in the Andersen Behavioural Model is participation in the necessary 150 minutes of physical exercise each week, while the independent variables are predisposing, enabling, and need factors. To determine whether individuals had met this criterion in the previous month, a binary logistic regression test was employed. About 31.9% of the 1,577 participants in the sample met the 150 minutes per week of physical exercise recommended by the World Health Organization (WHO). Among the important variables linked to physical exercise were age (aOR = 1.030, 95% CI 1.013 to 1.047), awareness about healthy living community movement program (aOR = 1.45, 95% CI 1.135 to 1.852), and motivation to engage in physical activity (aOR = 3.653, 95% CI 1.382 to 9.656). Lower engagement was observed in males (aOR = 0.730, 95% CI 0.553 to 0.962) and Muslims (aOR = 0.511, 95% CI 0.296 to 0.883). Enabling factors that also had a substantial impact on physical activity engagement included community empowerment for communal physical exercise (aOR = 1.634), the availability of public sports facilities (aOR = 1.333), and flexible work schedules (aOR = 1.869). BMI and routine health examinations were not found to be significantly related need variables. Providing accessible physical activity spaces, encouraging communities to participate in group activities, and increasing awareness of healthy living initiatives are all necessary to strengthen the national NCD policy. Nurses and healthcare professionals play a pivotal role in this process by acting as health educators, advocates, and role models for healthy living. They can provide targeted health education, support behavior change interventions, and collaborate with community stakeholders to promote and sustain active lifestyles. This study emphasizes how crucial it is to incorporate physical activity promotion into nursing practice and public health initiatives in order to counteract the rising prevalence of NCD, while emphasizing the need for nurses and healthcare professionals to incorporate evidence-based strategies into patient care, prioritize preventive measures, and advocate for policies that support healthier communities.